1919 Tex. Gen. Laws 297-98, An Act to Preserve, Propagate, Distribute, and Protect the Wild Game, Wild Birds, Wild Fowl of the State . . . , ch. 157, § 42. - (:unkn) unknown (My University, 1919)
It shall be unlawful for any citizen of this State to hunt outside of the county of his residence with a gun without first having procured from the Game, Fish and Oyster Commissioner or one of his deputies or from the County Clerk of the County in which he resides a license to hunt, and for which he shall pay to the officer from whom he secures such license the sum of two ($2.00) dollars. . . Any person hunting any game or birds protected by the laws of the State, and who shall refuse to show his license herein provided for to any sheriff . . . on demand shall be deemed guilty of a violation of the provisions of this law, and any person violating any of the provisions of this Section shall be deemed guilty of a misdemeanor, and upon conviction shall be fined in a sum of not less than ten (10.00) dollars nor more than one hundred (100.00) dollars.
Keywords: HUNTING REGULATION